Variation in coagulation factor activity levels cause discrepancies between activated partial thromboplastin time and anti-Xa activity for heparin monitoring: a retrospective observational study - Tomoyo Saito; Mineji Hayakawa; Osamu Kumano; Yoshinori Honma; Mone Murashita; Jun Kato; Syouki Fukui; Masaki Takahashi; Yuki Takahashi; Takumi Tsuchida; Asumi Mizugaki; Shuhei Takauji; et al. (Journal of Intensive Care, 2023)
Abstract Background Unfractionated heparin (UFH) is primarily monitored using activated partial thromboplastin time (APTT). However, the recent introduction of anti-activated factor X (anti-Xa) activity testing has provided a direct evaluation of Xa inhibition by anticoagulants. This study aimed to investigate discrepancies between APTT and anti-Xa activity during UFH monitoring in critically ill patients and explore their underlying causes. Methods This study analyzed 271 pairs of laboratory test results from blood samples of 99 critically ill patients receiving continuous intravenous UFH. Theoretical APTT values were calculated using fitted curve equations from spiked sample measurements with anti-Xa activity. Samples were categorized into three groups based on the measurement of the APTT/theoretical APTT ratio: the lower group (< 80%), the concordant group (80–120%), and the upper group (> 120%). Results The overall concordance rate between APTT and anti-Xa activity was 45%, with a 55% discrepancy rate. The lower group frequently showed apparent heparin overdoses, while coagulation factor activities in the lower and upper groups were higher and lower, respectively, than those in the concordant group. Particularly, the lower group exhibited higher factor VIII activity levels than the upper and concordant groups. Conclusions Discrepancies between APTT and anti-Xa activity were frequently observed, influenced by changes in coagulation factors activity levels. The lower and upper groups were classified as pseudo-heparin-resistant and coagulopathy types, respectively. Accurate monitoring of heparin in critically ill patients is crucial, especially in cases of pseudo-heparin resistance, where APTT values may wrongly indicate inadequate heparin dosing despite sufficient anti-Xa activity. Understanding these discrepancies is important for managing heparin therapy in critically ill patients. Trial registration: Not applicable.